High Expression of microRNA-223 Indicates a Good Prognosis in Triple-Negative Breast Cancer - Chen, Li; Zhu, Xiuzhi; Han, Boyue; Ji, Lei; Yao, Ling; Wang, Zhonghua (Frontiers in Oncology, 2021)
Purpose: MicroRNAs can influence many biological processes and have shown promise as cancer biomarkers. Few studies have focused on the expression of microRNA-223 (miR-223) and its precise role in breast cancer (BC). We aimed to examine the expression level of miR-223 and its prognostic value in BC. Methods: Tissue microarray (TMA)-based miRNA detection in situ hybridization (ISH) with a locked nucleic acid (LNA) probe was used to detect miR-223 expression in 450 BC tissue samples. Overall survival (OS) and disease-free survival (DFS) were compared between two groups using the Kaplan-Meier method and Cox regression model. Results: OS and DFS were prolonged in the high miR-223 expression group compared to the low miR-223 expression group (p<0.0001 and p=0.017, respectively), especially in patients with the triple-negative breast cancer (TNBC) subtype (p=0.046 and p<0.001, respectively). Univariate and multivariate Cox regression analyses revealed that TNM stage (p=0.008), the molecular subtype (p=0.049) and miR-223 (p<0.001) were independently associated with OS and DFS. External validation was performed with the METABRIC and The Cancer Genome Atlas (TCGA) databases via online webtools and was consistent with the data described above. Conclusions: This study provides evidence that high miR-223 expression at diagnosis is associated with improved DFS and OS for BC patients, especially those with the TNBC subtype. miR-223 is a valid and independent prognostic biomarker in BC.